Risk factors and complications of small for gestational age - Liu, Qiang (Pak J Med Sci, 2019)
OBJECTIVE: The objective of this study was to find out the maternal risk factors and perinatal complications in small for gestational age (SGA) newborns. METHODS: A total of 181 SGA cases and 1299 cases of appropriate for gestational age (AGA) with the same gestational age between January 2015 and December 2016 were enrolled in Linyi People’s Hospital, China. The risk factors were analyzed and the frequencies of perinatal complications were compared between the two groups. RESULTS: The frequencies of maternal risk factors such as pregnancy-induced hypertension, abnormal placenta and twins in the SGA group were significantly higher than that in the AGA group (P<0.05). The incidence of hyperbilirubinemia and hypoglycemia in the perinatal period was also higher in the SGA newborns group (P<0.05), while there were no significant differences in the incidence of pneumonia, apnea, septicemia, intracranial hemorrhage, neonatal asphyxia, congenital malformations, hypoxic-ischemic encephalopathy, respiratory distress syndrome and necrotizing enterocolitis between the two groups. CONCLUSIONS: SGA can cause perinatal complications including neonatal hypoglycemia and hyperbilirubinemia. It is necessary to strengthen the perinatal monitoring and antenatal care to reduce SGA and the perinatal complications of SGA.